Inconsistency of lesion quantitative assessment in 2D SUV and 3D SUV quantification techniques for [18F]-FDG PET/CT: a phantom study - Hanafi, Muhammad Hafiz; Mohd Noor, Noramaliza; Hassan, Muhammad Hishar (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
This study was performed to assess the inconsistency of lesion quantification in standardised uptake value (SUV) [ 18F]-FDG between Ellipse (2-Dimensional) and Ellipsoid (3-Dimensional) quantification techniques by using PET/ CT image quality phantom. Reconstructed images of PET/CT ACR phantom was used to assess the quantification of SUV (SUVmax, SUVavg and SUVmin) on selected regions of interest. Statistical analysis of paired t-test was performed to compare the lesion quantification in SUV [18F]-FDG between 2D and 3D techniques. The quantification techniques were consistently similar of assessment between 2D SUVmax and 3D SUVmax at 12mm of ROI lesion with [(0.00 ± 0.02), t(29)=-0.48, p>0.05]. However, the rest of quantification techniques of 2D SUVmax, 3D SUVmax, 2D SUVavg, 3D SUVavg, 2D SUVmin and 3D SUVmin, results shown significant inconsistency since the p >0.05]. However, the rest of quantification techniques of 2D SUVmax, 3D SUVmax, 2D SUVavg, 3D SUVavg, 2D SUVmin and 3D SUVmin, results shown significant inconsistency since the p<0.05. This phantom study has proven that there were inconsistency of lesion quantitative assessment in 2D SUV and 3D SUV quantification techniques for [18F]-FDG PET/CT.